SPREAD OF SCOTS PINE STANDS DECLINE IN KOROSTYSHIV FOREST ENTERPRISE - Andreieva, O. Y.; Goychuk, A. F. (Forestry and Forest Melioration, 2018)
Introduction Health condition of Scots pine (Pinus sylvestris L.) stands worsens in recent decades in many regions, including northern and southern countries as well as Belarus and Ukraine. Stem pests are the most visible cause of pine decline. However, tree resistance to infestation decreases as a result of climate change and anthropogenic impact. Pine engraver beetle Ips acuminatus (Gyllenhal, 1827) and six-toothed bark beetle Ips sexdentatus (Boerner, 1767) (Curculionidae, Scolytinae) have advantages due to monovoltinity. Pine engraver beetle infests the top of stem and branches both in living and felled trees, and six-toothed bark beetle infests stem butts. Both bark beetles are the vectors of pathogenic fungi. Investigation of stem insect foci development and spread show its diversity in different regions and stands, owing to climatic features and tree reaction on it. The aim of our research was to reveal the features of Scots pine decline in Zhytomyr (Central) Polissya on the example of Korostyshiv Forest Enterprise. Materials and Methods The investigations included a statistical and comparative analysis of forest fund database of the State Association “Ukrderzhlisproekt”, the data of forest pathological survey of pine stands in Korostyshiv Forest Enterprise and reports on sanitary felling in 2014–2017. Monthly air temperature and precipitation datasets were taken from Zhytomyr meteorological station (50°15' N 28°39' E). Selyaninov’s Hydro-thermal Coefficient – HTC (Selyaninov, 1937) was calculated. Statistical analysis was carried out with the help of MS Excel software. A tetrachoric correlation was evaluated to compare pine stands distribution by stand composition, age, and stocking density in the foci of bark beetles and in other pine stands, and the reliability was assessed by ?2 criterion. Results and Conclusions In Korostyshiv Forest Enterprise the proportion of selective felling in Scots pine decline foci was close to 100 % in 2014 and exceeded 80 % in other years. The main causes of Scots pine decline were bark beetles (72.4–95.8 %), fungal diseases (0.4–9.1 %) and weather conditions (3.5–27.5 %) Scots pine forest decline developed most often in pure Scots pine stands older than 50 years. The average weighted relative density of stocking was 0.7 and 0.71 in declining and non-declining Scots pine stands. Climatic factors were inciting factor for forest decline, and bark beetle infestation was a contributing factor for it. 7 Figs., 14 Refs.